Wireless and Satellite Systems : 7th International Conference, WiSATS 2015, Bradford, UK, July 6-7, 2015. Revised Selected Papers - Pillai, Prashant; Hu, Yim Fun.; Otung, Ifiok; Giambene, Giovanni; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the proceedings of the 7th International Conference on Wireless and Satellite Services, WiSATS 2015, held in Bradford, UK, in July 2015. The conference was formerly known as the International Conference on Personal Satellite Services (PSATS) mainly covering topics in the satellite domain. As the scope of the conference widened to include wireless systems, the conference was renamed to WiSATS. The 29 revised papers were presented at the conference in three technical sessions and one special session on Network Coding for Satellites. WiSATS 2015 also hosted two workshops along with the main conference: The first workshop, Communication Applications in Smart Grid (CASG 2015), focused on the merging area of using communication technology within the electricity power grid for smart monitoring and control. The second workshop, Advanced Next-Generation Broadband Satellite Systems (BSS 2015), focused on the use of satellite systems for providing next-generation broadband services. .
Residential Energy Consumption Scheduling Techniques under Smart Grid Environment -- Residential Demand Response Algorithms: State-of-the- Art, Key Issues and Challenges -- A Roadmap for Domestic Load Modelling for Large-Scale Demand Management within Smart Grids -- Agent-Based Models for Electricity Markets Accounting for Smart Grid Participation Securing the information infrastructure for EV charging Capacity Enhancing Techniques for High Throughput Satellite Communications -- Intelligent Gateways Enabling Broadband Access via integrated Terrestrial and Satellite Systems -- Modeling the Lifecycle Greenhouse Gas Emissions of a Hybrid Satellite System -- Extending the usable Ka band spectrum for satellite communications: The CoRaSat project -- On the feasibility of Interference Estimation Techniques in Cognitive Satellite Environments with Impairments -- Technology Trends for Ka-Band Broadcasting Satellite Systems -- Evaluating the Performance of Next Generation Web Access via Satellite -- Multimodality in the rainfall drop size distribution in southern England -- Wireless sensor networks and satellite simulation Mission Analysis for the optimization of the GPS coverage for an Earth Observation Satellite -- Proposal of Time Domain Channel Estimation Method for MIMO-OFDM Systems -- An OFDM Timing Synchronization Method Based on Averaging the Correlations of Preamble Symbol A Printed Wideband MIMO antenna for Mobile and Portable communication devices A new approach for implementing QO-STBC over OFDM -- Network coding for Multicast Communications over Satellite Networks Network Coding Over SATCOM: Lessons Learned -- Network Coding Applications to High Bit-Rate -- Can network coding mitigate TCP-induced queue oscillation on narrowband satellite links? -- Network coding over satellite: from theory to design and performance -- Gateway selection optimization in Hybrid MANET-Satellite network -- A Pragmatic Evaluation of Distance Vector Proactive Routing in MANETs via Open Space -- Elastic Call Admission Control using Fuzzy Logic in Virtualized Cloud Radio Base Stations -- Technology Impact on Agricultural Productivity: A Review of Precision Agriculture using Unmanned Aerial Vehicles.
Keywords: Computer Communication Networks; Telecommunication; Computer Communication Networks; Communications Engineering, Networks; Information Systems Applications (incl. Internet).